Residual Energy-Aware Clustering Transformation for LEACH Protocol - P. Ullas; K. S. Shivaprakasha (Journal of Telecommunications and Information Technology, 2021)
Energy is one of the crucial performance parameters in wireless sensor networks (WSNs). Enhancement of network lifetime is an important consideration as well. Low energy-aware clustering hierarchy (LEACH) is one of the protocols proposed for WSNs. In this paper, a residual energy-aware clustering transformation protocol for LEACH (REACT-LEACH), enhancing performance of LEACH by introducing a clustering mechanism, is proposed. The proposed cluster head (CH) rotation and cluster reformation processes are more effective in REACT-LEACH, as residual energy is considered to be one of the metrics. Performance of REACT-LEACH is validated based on simulations